Ectomycorrhizal symbiosis in declining and non-declining Quercus ilex trees infected with or free of Phytophthora cinnamomi - Corcobado, Tamara; Vivas, María; Moreno, Gerardo; Solla, Alejandro (Forest Ecology and Management, 2014)
Quercus ilex decline and the presence of the soil-borne pathogen Phytophthora cinnamomi are hypothesised to be associated with shifts in ectomycorrhizal fungi abundance. Soil properties may also influence the relation of this pathogen to ectomycorrhizae. To investigate these associations, 96 Q. ilex declining stands were selected in western Spain and both declining and non-declining trees were sampled. Soil properties (soil depth, Ah horizon thickness, texture, pH, redox potential, soil bulk density and N–NH4+ and N–NO3− concentrations), P. cinnamomi root infections and ectomycorrhizal fungi abundance were assessed. The most dominant ectomycorrhizal morphotypes were Cenococcum geophilum, Tomentella spp. and Russula spp. Lower percentages of non-vital and vital ectomycorrhizal root tips were observed in declining than in non-declining trees. No significant differences in parameters characterising the ectomycorrhizal community between trees infected with or free of P. cinnamomi were observed. However, results indicate that non-mycorrhizal root tips are vulnerable entry points for the pathogen into the tree. More tips were colonised by Russula spp. and other ectomycorrhizal fungi in non-declining infected trees than in declining infected trees. Trees growing on stream banks showed a lower abundance of ectomycorrhizal root tips in fine-textured soils than in coarse-textured soils. Ectomycorrhizal tip abundance was positively related to Ah horizon thickness, irrespective of tree health status. The presence of P. cinnamomi altered relations between ectomycorrhizal abundance and several soil properties. The limited ectomycorrhizal diversity in Q. ilex declining stands and interactions of ectomycorrhizal abundance with soil texture, topography and P. cinnamomi root infections are reported and discussed.
Keywords: Ectomycorrhizae; Iberian dehesa; Invasive pathogen; Oak decline; Soil fertility